Analytic Approach and Monte Carlo Sampling for Electron Correlations - Ghiringhelli, Luca M.; Site, Luigi Delle (Recent Progress in Orbital-free Density Functional Theory, 2013)
By combining rigorous mathematical conditions and a computational approach for sampling the electronic configurations in space, we build a procedure for the design of kinetic functionals for electrons which is internally consistent. We then apply it to the test case of the almost uniform interacting electron gas and derive the corresponding kinetic functional. Interestingly the functional form obtained has strong similarities with the Shannon Entropy within the Theory of Information.
CRIS-Team Scopus Importer:2023-09-25